Making Decisions About Potentially Life-Sustaining Treatment at End of Life: A Metasynthesis Exploring Relational Dynamics and Healthcare Philosophies - Montanaro, Palmina (Université d'Ottawa / University of Ottawa, 2022)
Background: Decisions about potentially life-sustaining treatment are often not raised with patients and families until end of life (if at all), and are influenced by their many relationships. Objective: Understand how patients and families' relationships impacted their experiences of making these decisions, and how healthcare philosophies impacted authors' portrayal of these experiences. Methods: Qualitative metasynthesis design. Purposeful sampling was used to select the 19 qualitative studies included. Relational ethics and meta-study (an approach to metasynthesis) guided data collection and analysis. Findings: 1) Closeness in relationships was valued. Healthcare professionals' (dis)honesty and (lack of) empathy affected closeness with patients/families; 2) Patients' identity and quality of life was considered in decisions, and was maintained through close relationships; 3) Reliance on relationships occurred for information, care and support; 4) Decision makers felt a sense of responsibility to consider their relationships when deliberating treatments; 5) Normative discourses were reflected in authors' writing.
Keywords: End of life; Life sustaining treatment; Decision making; Patients and families; Relational ethics